Pemanfaatan Karbon Batang Jagung (Zea mays) untuk Penjernihan Minyak Jelantah - Karsa, Dion Randi; Putra, Ananda; Sanjaya, Hary; Novel, Dheo Shalsabilla; Izanel, Rezi Ananta; Putri, Natasya Alya; Khaliq, Feni Kurnia; Jannah, Miftahul; Nizar, Umar Kalmar (Periodic, 2025)
Used cooking oil, which is often discarded carelessly, can cause environmental pollution and adversely affect health if consumed again. This study explored the use of activated carbon produced from corn stalks (Zea mays) for the purification of used cooking oil. Activated carbon was produced through chemical activation using NaOH and applied to used cooking oil in various treatments, including combination with cornstarch. The quality of the purified oil was evaluated based on density, flow rate, saponification number, and acid number. The results of this study are expected to provide an environmentally friendly solution in the treatment of used cooking oil waste and utilize corn stalk waste effectively, thereby reducing negative impacts on the environment and improving public health.The result of this study is activated carbon from corn stalks which is able to reduce the density of 0.83 g/mL with cornstarch adsorbent, flow rate of 0.201 ml/s with carbon adsorbent, acid number of 5.31 mg/KOH with carbon adsorbent, saponification number of 139.46 mg/KOH.